2020
DOI: 10.1101/2020.06.26.170555
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HLH-30 dependent rewiring of metabolism during starvation inC. elegans

Abstract: SummaryOne of the most fundamental challenges for all living organisms is to sense and respond to alternating nutritional conditions in order to adapt their metabolism and physiology to promote survival and achieve balanced growth. Here, we applied metabolomics and lipidomics to examine temporal regulation of metabolism during starvation in wildtype Caenorhabditis elegans and in animals lacking the transcription factor HLH-30. Our findings show for the first time that starvation alters the abundance of hundred… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The samples were analysed as in Dall et al [ 31 ]. In brief, 5 μL was injected using a 400 μl/min and the following composition of eluent A (0.1% formic acid) and eluent B (0.1% formic acid, acetonitrile) solvents: 3% B from 0 to 1.5 min, 3%–40% B from 1.5 to 4.5 min, 40%–95% B from 4.5 to 7.5 min, 95% B from 7.5 to 10.1 min and 95%–3% B from 10.1 to 10.5 min before equilibration for 3.5 min with the initial conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples were analysed as in Dall et al [ 31 ]. In brief, 5 μL was injected using a 400 μl/min and the following composition of eluent A (0.1% formic acid) and eluent B (0.1% formic acid, acetonitrile) solvents: 3% B from 0 to 1.5 min, 3%–40% B from 1.5 to 4.5 min, 40%–95% B from 4.5 to 7.5 min, 95% B from 7.5 to 10.1 min and 95%–3% B from 10.1 to 10.5 min before equilibration for 3.5 min with the initial conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The flow from the UPLC was coupled to a Q Exactive HF mass spectrometer (Thermo Fisher Scientific) for mass spectrometric analysis in both positive and negative ion modes. The raw data were also processed as in Dall et al [ 31 ] using MZmine (v 2.53) [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The raw data were also processed as in Dall et al (2021) using MZmine (v 2.53; Pluskal et al, 2010). Features were annotated by searching against NIST17 Tandem Mass Spectral Library, MoNA – MassBank of North America library and finally SIRUIS (v. 4.7.0 [Duhrkop et al, 2019]).…”
Section: Methodsmentioning
confidence: 99%
“…The samples were overall analyzed as in Dall et al (2021). In brief, 5 μl was injected on a Vanquish Horizon UPLC (Thermo Fisher Scientific) where a flow of 400 μl/min was used with the following composition of eluent A (0.1% formic acid) and eluent B (0.1% formic acid, acetonitrile): 3% B from 0 to 1.5 min, 3% to 40% B from 1.5 to 3 min, 40% to 95% B from 3 to 5 min, 95% B from 5 to 7.6 min and 95% to 3% B from 7.6 to 8 min before equilibration for 3.5 min with the initial conditions.…”
Section: Analyses Of Global Gene Expression By Rnaseqmentioning
confidence: 99%
“…Further analysis showed that hlh-30 mutants shift their metabolism from mitochondrial to peroxisomal beta-oxidation. Further knockdown of prx-5 , compromising the generation of peroxisomes, further rendered hlh-30 mutants hypersensitive to starvation [ 96 ].…”
Section: Applications Of C Elegans Metabolomicsmentioning
confidence: 99%